Baseline serum leptin predicts peritoneal dialysis adequacy: a single-center prospective, longitudinal study - Stepanova, N.; Burdeyna, O.; Driianska, V.; Ablogina, O. (Ukrainian Journal of Nephrology and Dialysis, 2018)
Hyperleptinemia is often observed in peritoneal dialysis (PD) patients. But, there are few studies on the relationship between blood leptin level and PD survival, and, some of them contradict each other. The present study aimed to investigate the impact of PD initiation on the serum leptin concentrations and its association with PD adequacy. Method. A total of 23 patients with end-stage renal disease (ESRD), who started the treatment with continuous ambulatory peritoneal dialysis (CAPD), were included in this prospective single-center observational longitudinal study. Among the patients, there were 15 men and 8 women; the average age of the patient population was 52.4 ± 12.3 years. The treatment with CAPD was performed using Dianeal PD 4 with glucose concentration of 1.36% and 2.27%. The patients were screened before PD initiation and after 3- and 12- month PD treatment. Leptin levels were determined in all patients using ELISA-method. Results. The median serum leptin concentration at study entry was 10.6 [5.6-21.9] ng/mL. Leptin level and its dynamics during the year after PD treatment initiation were dependent on body mass index (BMI). The overweight or obese patients had ever-increasing leptin levels after 3- and 12- month PD treatment. Whereas in the PD patients with normal weight, we observed a significant decrease of leptin levels after 12-month PD treatment. Serum leptin concentration in the women was significantly higher compared with the men (46.4 [1.1-95] vs 9.8 [3.2-14.5] ng/mL; p = 0.02). Blood cholesterol levels had a positive correlation with serum leptin concentrations after 3- and 12- month PD treatment: r = 0.53, p = 0.01 and r = 0.56, p = 0.008, respectively. However, we did not find a statistically significant association of leptin with PD adequacy parameters after 3- and 12- month PD treatment of the patients. In the Cox proportional hazard model adjusted for gender, serum leptin level demonstrated itself as the effective factor in PD adequacy survival: HR 5.3 (95% CI 1.7; 16.3). PD adequacy survival was better in the patients with leptin concentrations above the median (≥10.6 ng/mL) compared with the patients who had serum leptin levels below the median (log rank test, χ2 = 8.2; p = 0.0042). Conclusions. Our study have demonstrated markedly elevated serum leptin level in the overweight PD patients and its strong decrease during 12 months in the patients with normal weight. Low serum leptin level before PD initiation is associated with inadequate PD.